Morphology and defects design in g-C3N4 for efficient and simultaneous visible-light photocatalytic hydrogen production and selective oxidation of benzyl alcohol. (19th May 2022) - Liu, Xiaolei; Zhang, Qianqian; Cui, Zihao; Ma, Fahao; Guo, Yuhao; Wang, Zeyan; Liu, Yuanyuan; Zheng, Zhaoke; Cheng, Hefeng; Dai, Ying; Huang, Baibiao; Wang, Peng
Abstract: Small surface area, deficient reaction sites, and poor visible-light harvest ability of the original graphitic carbon nitride (g-C3 N4 ) severely restrict its photocatalytic H2 production activity. Here, an ultrathin porous and N vacancies rich g-C3 N4 (VN -UP-CN) was fabricated by thermal oxidation exfoliation and high-temperature calcination under the Ar atmosphere. The ultrathin porous morphology increases the surface area and reaction sites of original g-C3 N4, moreover, the produced N vacancies greatly broaden the light harvest ability of ultrathin porous g-C3 N4 (UP–CN). Therefore, VN -UP-CN displays the maximal H2 production rate of 2856.7 μmol g −1  h −1 in triethanolamine solution under visible-light, and adding 0.5 M of K2 HPO4 can further improve its H2 production rate to 4043.9 μmol g −1  h −1 . Importantly, VN -UP-CN also shows good performance in simultaneous photocatalytic H2 production and benzyl alcohol oxidation to benzaldehyde with the activities of 196.08 and 198.28 μmol g −1  h −1, respectively, which avoids the waste of sacrificial agent and photogenerated holes. This work affords an achievable way to design the efficient g-C3 N4 photocatalyst by morphology and defect regulation, which can effectively utilize both photogenerated electrons and holes for H2 and value-added chemical production. Graphical abstract: Image 1 Highlights: An ultrathin porous and N vacancies rich g-C3 N4 was successfully prepared. Structural advantage and expanded light absorption greatly improve the photocatalytic activity. Simultaneous photocatalytic H2 production and selective oxidation of benzyl alcohol are achieved. Photogenerated carriers are effectively utilized in this g-C3 N4 photocatalytic system.